Analisis Faktor Materi Dan Metode PAI Pada Pembinaan Akhlak Bagi Anak Usia Dini Di Keluarga Buruh Perkebunan Teh Pasir Malang Afdeling Riung Gunung Bandung Selatan - Basrawy, Joyce Bulan; Syahidin, Syahidin; Supriadi, Udin (Civilization Research: Journal of Islamic Studies, 2022)
The purpose of this study was to determine the model of early childhood Islamic Religious Education in the families of Afdeling Riung Gunung Pasir Malang Malang Tea Plantation workers. The method used in this study was qualitative with an ethnographic approach to identify, understand, and interpret social actions, social structure, and society culture. Data was collected by observation, including descriptions in detailed contexts accompanied by notes from the results of in-depth interviews and document analysis. The informants were workers in Riung Gunung who had early childhood, community leaders, and religious leaders. The results showed the way parents of tea plantation workers in internalizing moral values ​​to their children form a model called the "afdeling model"; which indirectly implemented moral values ​​to their children by teaching them material understanding of divinity, destiny, worship (prayer), and morality (adab), by applying methods of habituation, example, punishment, gifts, empathy, tarhib (threats), and story.